2006
DOI: 10.1158/0008-5472.can-05-4287
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-Assisted Pathway Analysis Identifies Mitogen-Activated Protein Kinase Signaling as a Mediator of Resistance to the Green Tea Polyphenol Epigallocatechin 3-Gallate in Her-2/neu–Overexpressing Breast Cancer Cells

Abstract: Overexpression of the epidermal growth factor receptor family member Her-2/neu in breast cancer leads to autophosphorylation of the receptor and induction of multiple downstream signaling pathways, including the Akt kinase to nuclear factor-nB (NF-nB) cascade that is associated with poor prognosis. Previously, we showed that the green tea polyphenol epigallocatechin 3-gallate (EGCG) inhibits growth of NF639 Her-2/neu-driven breast cancer cells via reducing receptor autophosphorylation and downstream Akt and NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…Indeed, our independent identification of the tumor suppressor PTEN [53] and of E-cadherin/Wnt/β-catenin signaling [54] as molecular pathways influenced by dietary exposure to SPI and GEN in vivo and by GEN in vitro has been bolstered by the recently elaborated linkage between these two signaling pathways in the regulation of normal and malignant mammary stem/progenitor cells in vivo and in vitro [55]. Similar support has been provided by other published studies, including those for epigallocatechin-3-gallate [56], phytoestrogens [57] and polyunsaturated fatty acids [58]. Taken together, the cellular pathways mediating dietary factor actions in the context of mammary epithelial growth regulation implicate their collective opposing actions on the expression and/or activity of tumor suppressors and oncogenes and their respective downstream targets.…”
Section: Dietary Factors and Mammary Epithelial Targets In Breast Cansupporting
confidence: 54%
“…Indeed, our independent identification of the tumor suppressor PTEN [53] and of E-cadherin/Wnt/β-catenin signaling [54] as molecular pathways influenced by dietary exposure to SPI and GEN in vivo and by GEN in vitro has been bolstered by the recently elaborated linkage between these two signaling pathways in the regulation of normal and malignant mammary stem/progenitor cells in vivo and in vitro [55]. Similar support has been provided by other published studies, including those for epigallocatechin-3-gallate [56], phytoestrogens [57] and polyunsaturated fatty acids [58]. Taken together, the cellular pathways mediating dietary factor actions in the context of mammary epithelial growth regulation implicate their collective opposing actions on the expression and/or activity of tumor suppressors and oncogenes and their respective downstream targets.…”
Section: Dietary Factors and Mammary Epithelial Targets In Breast Cansupporting
confidence: 54%
“…Nevertheless, about 5% of the NF639-HER-2-driven mouse mammary tumor cells showed resistance to EGCG (174.5 mM)-mediated inhibition. Guo et al 51 then characterized the latter by Western blot and microarray-assisted pathway analysis. 51 These resistant clones displayed (i) a loss of HER-2 tyrosine phosphorylation, (ii) an elevated NF-kB activity, and (iii) elevated phospho-ERK and phospho-c-jun, confirming the activation of MAPK pathway.…”
Section: Egcg Egc and Ecgmentioning
confidence: 99%
“…Guo et al 51 then characterized the latter by Western blot and microarray-assisted pathway analysis. 51 These resistant clones displayed (i) a loss of HER-2 tyrosine phosphorylation, (ii) an elevated NF-kB activity, and (iii) elevated phospho-ERK and phospho-c-jun, confirming the activation of MAPK pathway. Others 52 showed that EGCG significantly reduced (i) BT474 cell growth (IC 50 ¼ 65.4 mM), (ii) HER-2 phosphorylation without changing HER-2 total level, (iii) phosphorylated Stat3 and Stat3 levels in a time-dependent manner, (iv) inhibited c-fos and cyclin D1 promoter activities, and (v) decreased cyclin D1 and Bcl-XL expression levels.…”
Section: Egcg Egc and Ecgmentioning
confidence: 99%
“…Epigallocatechin-3-gallate (EGCG), a major polyphenol, which accounts for 10%-15% of the total green tea [12], was implicated as the main active ingredient. EGCG is a potent antioxidant that has attracted considerable attention for its role in preventing oxidative stress-related diseases including cancers, cardiovascular diseases and fibrosis [13][14][15]. Recently, Chen et al [16] have reported that in the mice model, the nonfibrotic hepatic damage induced by a single dose of CCl 4 was reduced following EGCG pretreatment.…”
Section: Introductionmentioning
confidence: 99%